Effect of Coping with Anxiety Education on Women’s Anxiety Level - Serpil Türkleş; Belkıs Karataş; Gülay Yılmaz (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Objective: This research was conducted for the purpose of determiningthe effect of coping anxiety education on women’s anxiety level. Method: The research population was comprised of 174 women whowere in families being followed as part of the Community HealthNursing course by 46 senior nursing students and who were registeredat two Primary Health Care Clinics between April 14 and May 14,2007. The research sample was comprised of 160 of these women, 80of whom were in the education group and 80 in the control group.Coping with anxiety education was given to the education group intwo sessions for a total of two hours and was given an educationbooklet. In the education, explanation, question-answer anddemonstration techniques were used.Results: The difference in the before and after coping with anxietyeducation Beck Anxiety Inventory BAI score means for the educationgroup was found to be significant p0.05 . Conclusion: Findings that were obtained show that anxietymanagement training in two one-hour sessions with a two weekinterval was effective in lowering women’s anxiety level